PEMBELAJARAN PADA MASA PANDEMI COVID-19 DI TPA AL HUSNA BARAK, MARGOLUWIH, SEYEGAN, SLEMAN - Nabila Nauf Indriana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The COVID-19 pandemic has had a major impact on the world of formal and non-formal education. Education must be held by distance or what we call online learning, even though not all parties can adapt to this, especially people in rural areas. The Al Husna TPA, which is located in the countryside, also feels this obstacle. This study aims to find out how learning activities take place at the Al Husna Barak TPA during the pandemic and to find out the difference between learning carried out at the Al Husna TPA before the pandemic and during the pandemic. This study uses a qualitative descriptive method with interviews and observations as data collection techniques. At the beginning of the pandemic, Al Husna TPA eliminated learning activities. But a few months later, the lesson was finally held again. Learning at Al Husna TPA is held offline because it is not possible to hold it online. There are positive and negative differences in learning at Al Husna TPA after entering the COVID-19 pandemic. These differences include materials, participants, number of meetings, to facilities.